(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article, all important functions of the body - breathing, blood circulation, swallowing, urination, defecation, movement of the body in space are ultimately performed by muscle contraction. Information related to the function of skeletal muscles of any human movement is presented.